USABILITY AS A WAY TO IMPROVE THE EFFECTIVENESS OF INFORMATION SYSTEMS IMPLEMENTATION (Journal of Information Technologies in Education (ITE), 2015)
Lately, the information systems of different types, particularly systems to manage scientific research, have been widely introduced into education and science. However, the ways of optimizing the implementation of such systems as well as the improvement of their effectiveness have not beenadequately studied. That is why further research is needed for possible ways of improving the information systems implementation. The effectiveness of the information systems implementation is largely dependent on the presence of a "friendly" interface system, on its usability.     The goal of the paper is to determine the theoretical aspects of the "usability" concept and to study how the usability improves the efficiency of information systems in scientific research management. The subject of this research is to study the usability as a means of improving information systems efficiency using as an example the information system to manage scientific research at the National Academy of Pedagogical Sciences of Ukraine. This paper examines the main approaches to the evaluation of information systems usability. The paper also describes the testing of information system usability in research management. The research made it possible to conclude that the usability is a factor that increases the efficiency of an information system and allows potential users to better understand, organize and summarize business processes.     Although the application of the principles of usability is a promising direction, it is one of the little studied problems in the Ukrainian systems engineering. The detailed study of usability basic rules will allow developers of information systems to create better products with "friendly" interfaces. These rules will help users better understand the content of newly created information resources and therefore will facilitate their implementation and usage.
Keywords: an information system; management; scientific research; usability